Use of virtual reality in children undergoing surgery - Bezgin, Sabiha; Hüzmeli, İrem; Katayıfçı, Nihan; Yıldırım, Bilgi Asena; Atıcı, Ahmet (Frontiers in Pediatrics, 2025)
ObjectiveEarly mobilization and exercise after surgery are very important to reduce the impact on respiratory system function. The aim of this study was to compare the effects of early mobilization with virtual reality and conventional physiotherapy methods on pulmonary function, dyspnea, exercise capacity, pain, and kinesiophobia in children undergoing surgery.MethodsChildren aged 5–18 years who underwent various surgeries were randomly assigned to either a control group receiving conventional physiotherapy or a virtual reality group receiving additional virtual reality-based interventions. Interventions began on the day of surgery after anesthesia effects subsided and continued twice daily for two days. Outcome measures were performed before surgery and before discharge included pulmonary function tests, respiratory muscle strength, dyspnea, exercise capacity, dynamic balance, pain and kinesiophobia. Randomization was conducted using sealed-envelope drawing, and assessments were performed by a blinded physiotherapist.ResultsA total of 27 children were included in the study, with 14 children in the control group and 13 children in the virtual reality group. When we analysed the results of pulmonary function tests, we observed that maximum inspiratory pressure increased in both groups, whereas maximum expiratory pressure increased only in the virtual reality group (p = .01). As a result, there was no difference in dyspnea, exercise capacity, dynamic balance, pain, and kinesiophobia in both groups (p > .05).ConclusionIn conclusion, we found that early physiotherapy was effective in the respiratory parameters of children undergoing surgery. Early mobilization with virtual reality improved the maximal expiratory pressure of children undergoing surgery. Thus, the virtual reality can serve as an alternative method to facilitate mobilization in children. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT06882382).